PENGARUH KEPUASAN TERHADAP LOYALITAS DENGAN SWITCHING COST SEBAGAI VARIABEL INTERVENING PADA PELANGGAN PROVIDER PREPAID TELKOMSEL DI KOTA MEDAN - Hutapea, Katrin Evalastri; Ginting, Paham; Ginting, Paham; Sutarman, Sutarman; Sutarman, Sutarman (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
Telecommunication companies in Indonesia are now in slack condition. They are not able to apply the strategy of market expansion to increase their profit. Therefore, maintaining customer loyalty is one of the best ways to satisfy customers. However, customer satisfaction is not enough to maintain customer loyalty since competitors also apply the same thing. In order to forestall the move of customers, it is necessary to apply switching cost strategy. The objective of the research was to find out the influence of satisfaction on loyalty through switching cost in Telkomsel customers in Medan.The samples were 160 respondents, taken by using convenience sampling technique. The data were gathered by using likert instrument and analyzed by using descriptive analysis, cross tabulation, and partial least square (PLS). The result of the research showed that all hypotheses could be confirmed. Satisfaction had positive influence on switching cost, switching cost had positive influence on loyalty, and satisfaction had positive influence on loyalty. However, in this research, switching cost could not mediate the influence of consumer satisfaction on loyalty. Direct influence of satisfaction on customer loyalty was higher than that through switching cost.Keywords: Satisfaction, Switching Cost, Loyalty